Evaluation of the quality of staff and management support on the effectiveness of accounting information systems - Paschal Vishnu Rasto Karnantio (IHSA Institute, 2022)
The purpose of this study was to examine the effect of staff quality and management support on the effectiveness of accounting information systems, either partially or simultaneously. This type of research is a type of correlational research, which aims to find whether there is a relationship between two or more variables. Data collection techniques used are interviews, observation, documentation, questionnaires. The data analysis techniques used were: (1) To determine the partial effect of staff knowledge of technology, training, technical skills, and management support on the variable effectiveness of accounting information systems, namely through the t test. (2) To determine the simultaneous effect of staff knowledge on technology, training, technical ability, and management support for the variable effectiveness of the accounting information system, namely through the F test. Based on the results of the analysis that has been carried out, it can be concluded that the variables of staff knowledge of technology and staff training variables partially have no positive effect, while the variables of technical ability and management support partially have a positive effect. Through the F test it can be concluded that simultaneously there is a variable influence of staff knowledge of technology, staff training, technical skills, and management support on the effectiveness of the accounting information system. while the variables of technical ability and management support partially have a positive effect. Through the F test it can be concluded that simultaneously there is a variable influence of staff knowledge of technology, staff training, technical skills, and management support on the effectiveness of the accounting information system. while the variables of technical ability and management support partially have a positive effect. Through the F test it can be concluded that simultaneously there is a variable influence of staff knowledge of technology, staff training, technical skills, and management support on the effectiveness of the accounting information system.